Reproductive Ecology of the Java Rabbitfish, Siganus javus, in the Southern South China Sea - Takaomi Arai; Tan, Iy Vonne; Ching, Fui Fui; Norhayati Ahmad (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Fish reproductive biology influences their life history and can impact their vulnerability to fisheries; therefore, for sustainable management and development, a proper understanding is crucial. Reproductive biology, including maturation, spawning season, fecundity, and sex ratio, was examined throughout the year in the Java Rabbitfish, Siganus javus, in the southern South China Sea. This study is the first to examine reproductive traits by collecting a total of 339 S. javus specimens monthly from September 2017 to August 2018 through detailed gonad histology. The spawning season of female S. javus was mainly restricted to July, August, October, and December, whereas male fish were found to spawn throughout the year. Inter-species variations in the spawning season were observed within the genus, which is influenced by interspecific spawning strategies and regional environmental factors. The sex ratio close to 1:1 suggests that the fish population is in equilibrium in the region. The fecundity of S. javus ranged from 1.8 × 105 to 12 × 105, which was similar to that of other species in Siganus, suggesting less inter- and intra-species variation in fecundity within the family. The middle maturation stage was absent throughout the year, probably due to the different habitat uses during their life history. Reproductive biology might influence other biological aspects, such as migration and behaviour in the fish.